Analysis of trace amounts of oxygen, carbon monoxide and carbon dioxide in nitrogen using gas chromatography - Rohwer, Egmont Richard (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2008.